Application Of The Inside Outside Circle (IOC) Learning Model To Improve History Learning Outcomes For Class X IPS 1 Students At SMA Negeri 1 Pangean - Bismi Arfedi; Isjoni Isjoni; Asril Asril (JURNAL PENDIDIKAN IPS, 2025)
The results of observations show that student learning outcomes in the History learning process are not optimal so that student learning outcomes become optimal learning models that are in accordance with the objectives, namely the Inside Outside Circle learning model for class X IPS 1 students of SMA Negeri 1 Pangean. This study uses Classroom Action Research, namely planning, implementation, observation, and reflection. The research instruments used the Teaching Module as an instrument for learning devices and data collection instruments are teacher observation sheets, student observation sheets and tests. The study was conducted using 2 cycles, including the first cycle with 2 meetings and the second cycle with 2 meetings. In analyzing the data obtained from the results of observations of teacher and student activities by calculating the activities carried out by teachers and students. in cycle 1 there were 13 students who completed and 17 students who did not complete 43.33% had not reached the desired target. While in cycle II, there were 26 students who completed and 4 students who did not complete, classically reaching 86.67%, this percentage reached a score above 85%.